Kewenangan Pemerintah Kabupaten dalam Pengelolaan Hutan Mangrove - Saddat, Anwar; Hartati, Hartati; Priskap, Ridham (Universitas Batanghari Jambi, 2025)
The government's authority in the field of forest conservation as stated in Article 27 paragraph (3) above is further emphasized in Law Number 14 of 1999 concerning Forestry, namely in Article 4. Meanwhile, the authority of the regional government regarding forest management is regulated in Law Number 41 of 1999 concerning Forestry in Articles 59 to 65. From Article 59 to Article 65 of Law Number 41 of 1999 concerning Forestry, the regional government also has authority in managing mangrove forests. The objectives of this study are 1) to determine and analyze the authority of the Regency government in managing Mangrove forests 2) to determine and analyze the Regency Government's Policy on mangrove forest management. This study uses normative legal research using the approach, legislation, conceptual approach), historical approach with an 8-month activity plan and the scope or object in this study regarding the authority of the district government in managing mangrove forests based on legal provisions related to legal issues, Collection of primary legal materials, secondary legal materials, and tertiary legal materials using a card system and supported by a computerization system via the internet. There are 3 data collection techniques, namely 1) inventory technique, 2) systematization technique, and 3) interpretation technique. Results: Mangrove damage caused by land conversion, from mangrove forests to settlements and trade, as well as illegal logging and uncontrolled utilization of resources by the surrounding community. The lack of maximum supervision of mangrove forests so that the local government takes a local government policy or the authority to control conversion in a top-down manner (firm policy) through socialization and providing incentives and disincentives for violators. As well as the policy of managing mangroves as coastal protectors so that the number of mangroves is maintained or even increased.